Measuring the effects of schooling on wages for a young sample from rural Guatemala - Alba, Michael M. (1996)
In order to measure the intrinsic effect of schooling on wages for adolescents and young adults from four villages in Rural Guatemala, this paper estimates different wage specifications that have been suggested in the human capital literature. Successively accounted for are potential sources of bias in the estimated coefficient of schooling, such a those arising from self-selectivity in the wage earning sample and for the omission of innate ability, family background, and the quality of schooling from the set of wage determinants. The results show that when these potential sources of bias are treated, the rate of return to schooling (inclusive of its cognitive and no cognitive aspects) is about 5.9 percent for the population of adolescents and young adults in these villages.
Keywords: Wages -- Effect of education on; Human capital; Young adults -- Guatemala